New Formulation for the Estimation of Monthly Average Daily Solar Irradiation for the Tropics: A Case Study of Peninsular Malaysia. (28th November 2013) - Shavalipour, Aghil; Hakemzadeh, Mir Hamed; Sopian, K.; Mohamed Haris, Sallehuddin; Zaidi, Saleem H.
Abstract : In order to investigate a potential use of concentrating solar power technologies and select an optimum site for these technologies, it is necessary to obtain information on the geographical distribution of monthly average daily solar irradiation over an area of interest. In this study, three different models (Paltridge, Daneshyar, and modified Daneshyar) for the estimation of solar irradiation were discussed, and it turns out that the best result belongs to modified daneshyar method. This modification was necessary in order to accommodate tropical climate condition. The modifications are made by the inclusion of altitude, monthly total number of cloudy days, and variation of Sun-Earth distance. Data were analyzed for one year starting from January till December 2009. The annual average daily solar radiation for Peninsular Malaysia, during one year, has been between 13.67 MJ·m −2 ·day −1 and 17.18 MJ·m −2 ·day −1 . The highest solar irradiation was estimated as 19.28 MJ·m −2 ·day −1 in the month of January, while the lowest was 10.53 MJ·m −2 ·day −1 recorded in November. The northern region has the highest potential for solar energy application due to its high solar irradiation throughout the year.